Reconstruction of Renewal of Community Development Methods in the World of Islamic Education in the Industrial 4.0 Era - Iswadi; Muntasir; M. Jafar; Halimatussa’diah; Irma Rahmayani; Lindayani (Britain International for Academic Research (BIAR) Publisher, 2020)
Time continues to rotate but the world of Islamic education, which is an inseparable part of the national education system, has the same role as one of the agents of social change, of course, the essence must still be maintained even though innovation changes with time and time shifts. Its existence and existence are also demanded to be able to compensate for the atmosphere of change (modernization) and the Industrial Era 4.0 or millennial era which penetrated into various aspects of life. In the current era (the era now) the world of education must reform with the pressure to create a more comprehensive and flexible education system, so that graduates can function effectively in the life of a democratic global society. Certainly the scientific tradition that developed rapidly in the Industrial Ages 4.0, aroused the awareness of scientists and the general public that mastery of science and technology is a must for the community. The progress and decline of society in the present and future is largely determined by the level of mastery of science, science and technology. This kind of awareness also has the potential to influence the development and efforts to revitalize Islamic scientific traditions.